Erythorbyl fatty acid ester as a multi-functional food emulsifier: Enzymatic synthesis, chemical identification, and functional characterization of erythorbyl myristate. (15th August 2021) - Park, Jun-Young; Myeong, Jaeho; Choi, Yoonseok; Yu, Hyunjong; Kwon, Chang Woo; Park, Kyung-Min; Chang, Pahn-Shick
Graphical abstract: Highlights: Erythorbyl myristate (EM) was regioselectively synthesized using immobilized lipase. The production yield of EM was 56.13 ± 2.51 mg EM/g myristic acid in GSL-MPS. The molecular structure of EM was identified as 6- O -myristoyl-erythorbic acid. EM showed amphiphilic property and micellar thermodynamic behavior. EM exhibited radical scavenging activity and bacteriostatic/bactericidal activities. Abstract: Erythorbyl myristate (EM), a potential multi-functional food emulsifier, was newly synthesized by immobilized lipase-catalyzed esterification between antioxidative erythorbic acid and antibacterial myristic acid. The yield and productivity of EM were 56.13 ± 2.51 mg EM/g myristic acid and 1.76 ± 0.08 mM/h, respectively. The molecular structure of EM was identified as ( R )-2-(( R )-3, 4-dihydroxy-5-oxo-2, 5-dihydrofuran-2-yl)-2-hydroxyethyl tetradecanoate using HPLC-ESI/MS and 2D [ 1 H– 1 H] NMR COSY. The hydrophilic-lipophilic balance of EM was 11.5, suggesting that EM could be proper to stabilize oil-in-water emulsions. Moreover, isothermal titration calorimetry demonstrated the micellar thermodynamic behavior of EM and determined its critical micelle concentration (0.36 mM). In terms of antioxidative property, EM exhibited the radical scavenging activity against DPPH (EC50 : 35.47 ± 0.13 μM) and ABTS (EC50 : 36.45 ± 1.98 μM) radicals. Finally, EM showed bacteriostatic and bactericidal activities against Gram-positive foodborne pathogens (minimum inhibitory concentration: 0.06–0.60 mM; minimum bactericidal concentration: 0.07–0.93 mM).